Axial capacity and stiffness of post-heated circular and square columns strengthened with carbon fiber reinforced polymer jackets. (October 2021) - Abadel, Aref A.; Khan, M. Iqbal; Masmoudi, Radhouane
Abstract: The exposure of reinforced concrete (RC) columns to elevated temperatures is detrimental to its axial capacity and stiffness. Selecting the proper strengthening technique to repair heat-damaged RC columns is critical to ensure that the axial capacity and stiffness are restored. This paper examines the performance of different strengthening schemes using carbon fiber reinforced polymer (CFRP) jackets and near-surface mounted (NSM) steel bars in repairing circular and square RC columns damaged due to the exposure to high elevated temperature. The tested columns were divided into three categories, un-heated and un-strengthened columns, post-heated and un-strengthened columns, and post-heated and strengthened columns. The heated columns were exposed to 600 °C for 3 h. Two strengthening schemes were evaluated. The first strengthening scheme consisted of unidirectional CFRP strips in combination with NSM steel bars. The second scheme consisted of strengthening with unidirectional CFRP strips only. All the columns were tested under axial compression until failure. The test results showed that exposure to elevated temperatures caused a reduction in the load-carrying capacity of 38% in circular columns and 29% in square columns. Both strengthening schemes were effective in restoring and exceeding (by approximately 16%) the initial load-carrying capacity of heat-damaged RC columns. The use of CFRP strips in combination with NSM steel bars was more effective in restoring the initial stiffness of the post-heated columns compared to using CFRP strips alone. The initial stiffness recovery was more pronounced in circular columns compared to square columns. Circular columns exhibited 15% higher initial stiffness when compared to the control columns before heat-exposure. For square columns, the initial stiffness was equivalent to the initial stiffness of the control RC columns before heat-exposure.